PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK HASIL BELAJARBAHASA INDONESIA SISWA KELAS I SD NEGERI 012 PANGKALAN BARU KECAMATAN SIAK HULU - Arisah Arisah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This research was motivated by the low learning outcomes of Indonesian students at grade 012 SD Negeri Pangkalan Baru, withan average grade of 59.25. This research is a classroom action research (CAR). Aiming to improve the learning outcomes ofIndonesian students of class I SD Negeri 012 Pangkalan Baru. The subjects of this study were class I students of SD Negeri 012Pangkalan Baru, which amounted to 40 heterogeneous people. The data used in this study is data about the results of learningIndonesian. This study presents learning outcomes obtained from odd semester grades. The learning outcomes that occur frombefore the CAR is held with an average of 65.5 in the less category, while after the classroom action research in cycle I with anaverage of 65.5 with sufficient categories and in cycle II with an average of 71 in the good category. So the increase between thebasic score of the first cycle is 10.54% while the basic score of the second cycle is 19.83%. The results of this study prove thatthe application of the contextual teaching and learning model (CTL) can improve the learning outcomes of Indonesian studentsin class I SD Negeri 012 Pangkalan Baru.